2021
DOI: 10.11594/ijmaber.02.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Mastering Innovations in the Lens of Information and Communications Technology (ICT) Competence and Practices of 21stCentury Filipino Teachers: A Comparison among Thailand, Vietnam, and the Philippines

Abstract: In the advent of Information and Communications Technology in education, competence and skills for technology-based instruction are essential for teachers. With this, there is a need to continually train and equip teachers with understanding and capabilities that will enable them to maximize the utilization of ICT in their instructional practices. Hence, this research determined the correlation of teachers' level of ICT competence towards their ICT integration practices and corrobor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The finding conforms the following study: Gamboa & Gamboa [28] revealed that teachers are highly competent on MS Word, MS Excel and MS PowerPoint; Javier [29] claimed that most teachers are 'good' in ICT skills to utilized ICT tools and applications for teaching with the internet; Nueva [30] showed that teachers have high level of perceived technology integration practices; Albacete & Banhaw [31] revealed that Filipino found convenience and ease on the practice of technology integration; Ruman & Praksha [32] used TIM in measuring the extent of technology integration among teachers to facilitate their lesson; DeCoito & Richardson [33] proposed professional development opportunities for instructors to learn about the interaction of 21st Century Digital Skills, Technology Integration in Instruction and Challenges Encountered by Senior High School Teachers in Muntinlupa National High School technology, pedagogy, and subject matter; Hero et al [34] reported that Filipino teachers highly practiced the ICT integration as part of their instructional practices and strategies in teaching; Samote & De Guzman [35] describe public school teachers are advanced on the ICT competencies and technological operations; Lestiyanawati [36] indicated that online chat, using video conference, and combining both online chat and video conference in online teaching and learning process were the teaching strategies applied by teacher with the aid of technology; and Hero [37] affirmed that technology integration in instruction helps and assists teachers to bridge the gap between traditional teaching approaches and technology-based teaching and learning tools and facilities. 4 displays that Internet connection ranks one (1) as the challenge encountered by Senior High School teachers in technology integration in instructions based on weighted mean of 3.55.…”
Section: Very Highmentioning
confidence: 99%
“…The finding conforms the following study: Gamboa & Gamboa [28] revealed that teachers are highly competent on MS Word, MS Excel and MS PowerPoint; Javier [29] claimed that most teachers are 'good' in ICT skills to utilized ICT tools and applications for teaching with the internet; Nueva [30] showed that teachers have high level of perceived technology integration practices; Albacete & Banhaw [31] revealed that Filipino found convenience and ease on the practice of technology integration; Ruman & Praksha [32] used TIM in measuring the extent of technology integration among teachers to facilitate their lesson; DeCoito & Richardson [33] proposed professional development opportunities for instructors to learn about the interaction of 21st Century Digital Skills, Technology Integration in Instruction and Challenges Encountered by Senior High School Teachers in Muntinlupa National High School technology, pedagogy, and subject matter; Hero et al [34] reported that Filipino teachers highly practiced the ICT integration as part of their instructional practices and strategies in teaching; Samote & De Guzman [35] describe public school teachers are advanced on the ICT competencies and technological operations; Lestiyanawati [36] indicated that online chat, using video conference, and combining both online chat and video conference in online teaching and learning process were the teaching strategies applied by teacher with the aid of technology; and Hero [37] affirmed that technology integration in instruction helps and assists teachers to bridge the gap between traditional teaching approaches and technology-based teaching and learning tools and facilities. 4 displays that Internet connection ranks one (1) as the challenge encountered by Senior High School teachers in technology integration in instructions based on weighted mean of 3.55.…”
Section: Very Highmentioning
confidence: 99%